Placental growth factor and vascular endothelial growth factor serum levels in Tunisian Arab women with suspected preeclampsia. (March 2016) - Ben Ali Gannoun, Marwa; Bourrelly, Séverine; Raguema, Nozha; Zitouni, Hedia; Nouvellon, Eva; Maleh, Wided; Brahim Chemili, Afraa; Elfeleh, Raja; Almawi, Wassim; Mahjoub, Touhami; Gris, Jean-Christophe
Highlights: We quantitated the PIGF and VEGF plasma levels in Tunisian Arab women. We established the range of VEGF and PIGF in normal healthy pregnancies. Reduced PIGF levels are associated with subsequent development of preeclampsia (PE). VEGF levels were significantly lower in women with PE during early gestation age. The gestational age interval adjusted-5 th percentiles of PIGF provide reference ranges. Abstract: The angiogenic factors vascular endothelial growth factor (VEGF) and placental growth factor (PIGF) play a central role in the process of angiogenesis. We evaluated the association of free PIGF and free VEGF levels and the risk of preeclampsia (PE) among Tunisian Arab women, and established the range of VEGF and PIGF in normal healthy pregnancies, between 24 and 42 weeks of gestation. This retrospective case-control study included 345 women with PE, and 289 women with uncomplicated pregnancies. PIGF and VEGF plasma levels were quantitated by commercially-available ELISA. Compared to control women, plasma PIGF concentrations were lower in women with PE at all gestation age intervals ( P < 0.0001), compared to VEGF levels which were significantly lower in women with PE but only during early gestation age intervals ([29–32[ and [32–35[). High odds for developing PE, and correspondingly higher associations, were associated with low PIGF values (less than the 5 th percentile), at all gestation age intervals. The only exception was recorded for the [29–32 [interval, which was not statistically significant. PIGF testing, recorded at 29–37 weeks of gestation, had a higher specificity (93–100%) than sensitivity, and the positive predictive values ranged from 90% to 100% for 24–37 weeks of gestation. This indicates that it mainly detects non-PE healthy women as well, and thus may be useful as a screening test, though currently unreliable for diagnostic purposes. Reduced PIGF levels during different gestation age intervals, and reduced VEGF levels during early gestation age intervals are also associated with subsequent development of PE in our population; the gestational age interval adjusted-5 th percentiles of PIGF provide reference ranges for this marker in normal pregnancy.